PENGARUH PENGGUNAAN BINDER WAX TERHADAP HASIL ANALISIS KADAR NIKEL METODE PRESS PELLET MENGGUNAKAN WD XRF S8 TIGER - Iskandar, Ikram; Gala, Selfina (UIR Press, 2026)
This research is motivated by the absence of simultaneous optimization between the binder wax ratio and pressing pressure in the pressed pellet method for laterite nickel content analysis using WD-XRF. Previous studies generally only evaluated one preparation parameter separately, so the effect of the interaction of the two variables on accuracy and precision has not been comprehensively studied. This study aims to evaluate the effect of the binder wax ratio and pressing pressure on the results of nickel content analysis and compare them with Certified Reference Material (CRM). The research method includes the preparation of nickel ore samples through a process of drying, crushing, and sieving to a fine size. The samples were then mixed with binder wax at variations of 1.5%, 2.0%, and 2.5%, then pressed into pellets at pressures of 15 psi, 20 psi, and 25 psi. Nickel content analysis was carried out using WD-XRF. The results showed that the Ni content was in the range of 1.58–1.64%, higher than the CRM of 1.48%, with a difference of approximately 0.10–0.16%. This difference indicates the possibility of systematic bias in the form of overestimation which can be caused by matrix effects, particle size effects, or calibration drift. The addition of binder wax significantly reduced Ni content due to the dilution effect, while pressing pressure did not significantly affect the content value, but increased the physical quality of the pellets. In addition, the characteristics of the samples from the limonite-saprolite transition zone at a depth of about five meters also contributed to nickel enrichment. Overall, the results of the study were influenced by preparation factors, analytical methods, and geochemical conditions of the samples.